Ibudilast Attenuates Folic Acid–Induced Acute Kidney Injury by Blocking Pyroptosis Through TLR4-Mediated NF-κB and MAPK Signaling Pathways - Li, Xue; Zou, Yu; Fu, Yuan-Yuan; Xing, Jia; Wang, Kai-Yue; Wan, Peng-Zhi; Wang, Mo; Zhai, Xiao-Yue (Frontiers in Pharmacology, 2021)
Folic acid (FA)-induced renal tubule damage, which is characterized by extensive inflammation, is a common model of acute kidney injury (AKI). Pyroptosis, a proinflammatory form of cell death due to the activation of inflammatory caspases, is involved in AKI progression. Ibudilast, a TLR4 antagonist, has been used in the clinic to exert an anti-inflammatory effect on asthma. However, researchers have not explored whether Ibudilast exerts a protective effect on AKI by inhibiting inflammation. In the present study, Ibudilast reversed FA-induced AKI in mice, as indicated by the reduced serum creatinine and urea nitrogen levels and improved renal pathology, as well as the downregulation of kidney injury marker (KIM)-1. In addition, Ibudilast significantly increased the production of the anti-inflammatory factor IL-10 while suppressing the secretion of the proinflammatory cytokine TNF-α and macrophage infiltration. Moreover, in the injured kidney, Ibudilast reduced the levels of both inflammasome markers (NLRP3) and pyroptosis-related proteins (caspase-1, IL1-β, IL-18, and GSDMD cleavage), and decreased the number of TUNEL-positive cells. Further mechanistic studies showed that Ibudilast administration inhibited the FA-induced upregulation of TLR4, blocked NF-κB nuclear translocation and reduced the phosphorylation of NF-κB and IκBα, p38, ERK and JNK. Thus, this study substantiates the protective effect of Ibudilast on FA-induced AKI in mice and suggests that protection might be achieved by reducing pyroptosis and inflammation, likely through the inhibition of TLR4-mediated NF-κB and MAPK signaling pathways.